Productividad y competitividad en la industria manufacturera en México y China: un análisis comparativo (1996-2007) - Gómez Torres, Laura Hayde (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
In the present work the manufacturing commerce of Mexico and China in an individual and bilateral way is examined, emphasizing the presupposed "menace” by the Asian country to the Mexican industry. In this sense the countries competitiveness of the nine divisions of the manufacturing industry are analyzed in order to contrast them with their productivity, therefore making it possible to observe the influence of the second to determine the first. For this intention the revealed comparative advantages of the countries are obtained with the methodology proposed by Vollrath (1991) this methodology is used to identify the competitive sectors of both countries and in the relation of exchange. Likewise, to obtain the total and partial productivity index the Methodology of Hernandez Laos (1993) is used. The analysis of the results apparently suggests that the competitiveness of the manufacturing industry of both countries is determined in some way by its productivity. Standing out for Mexico is the influence of the capital partial productivity and for China the partial labor productivity. Additionally, China ́s higher competitiveness in a comparative way for the divisions set stands out.

En el presente trabajo se examina el comercio de manufacturas de México y China de manera individual y en su relación bilateral, enfatizando la presupuesta “amenaza” del país asiático para la industria mexicana. En este sentido se analiza la competitividad de los países en las nueve divisiones de la industria manufacturera, para posteriormente ser contrastadas con su productividad, de manera que fuera posible observar la influencia de la segunda para determinar la primera. Para dicho fin se, obtienen las ventajas comparativas reveladas de los países con el método propuesto por Vollrath (1991) para identificar los sectores competitivos de ambos países y en la relación de intercambio. Asimismo para obtener los índices de productividad total y parcial se emplea la metodología de Hernández Laos (1993). El análisis de los resultados sugiere que aparentemente la competitividad de la industria manufacturera de los dos países se encuentra determinada en cierta medida por su productividad, destacándose la mayor influencia de la productividad parcial del capital para México y la productividad parcial del trabajo para China. Adicionalmente se destaca la mayor competitividad de China en sentido comparado en el conjunto de divisiones.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2010-0009; Relaciones comerciales; Productividad; VCR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/943